2018
DOI: 10.1101/275420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic control of hippocampal spatial coding resolution by local visual cues

Abstract: 1Animals can flexibly navigate in their environment. This ability is thought to rely on an 2 internal cognitive map. An open question concerns the influence of local sensory cues on the 3 cognitive map and notably their putative contribution to setting its spatial resolution. Here 4 we compared the firing of hippocampal principal cells in mice navigating virtual reality 5 environments in the presence or absence of local visual cues (virtual 3D objects). Objects 6 improved the spatial representation both quanti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 61 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…While here we focused on overall environmental novelty, the hippocampal place code is also heavily influenced by the density and salience of environmental cues (Manns & Eichenbaum 2009,Bourboulou et al 2019) and the presence of reinforcement (Hollup et al 2001, Zaremba et al 2017, Dupret et al 2010), representations of which may actively shape behavior (Robinson et al 2020). We searched for evidence of differential concentration of BTSP-like field formation along the virtual track, but found that the distribution was mainly uniform over space after regressing out the component correlated with velocity (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…While here we focused on overall environmental novelty, the hippocampal place code is also heavily influenced by the density and salience of environmental cues (Manns & Eichenbaum 2009,Bourboulou et al 2019) and the presence of reinforcement (Hollup et al 2001, Zaremba et al 2017, Dupret et al 2010), representations of which may actively shape behavior (Robinson et al 2020). We searched for evidence of differential concentration of BTSP-like field formation along the virtual track, but found that the distribution was mainly uniform over space after regressing out the component correlated with velocity (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Our results encapsulate prior findings that individual cells have more and larger fields in bigger spaces 11,13 , describing them in terms of a simple interaction between homeostatic balance at the population level and rate of perceptual change, which is naturally elevated near boundaries and cues. Equally, this same basic model accounts for the clustering of place fields around visual cues in a 1D VR 24 and the effect of manipulated visual gain on hippocampal place cells in a 1D and 2D VR 25,26 . This work also resonates with early geometric cue-based models of place cell activity which sought to describe place fields using Weber-like responses to environmental boundaries 16,17,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results suggest that such a sequential firing pattern was conserved at least between two VR environments (Figures 4A,B), suggesting that cue-locking cells may encode relative distances from the cues. In VR, CA1 pyramidal cells have been seen to exhibit spatial activity that is strongly modulated by distinct visual cues (Bourboulou et al, 2018) and similarly, even in the open field, place cell firing can be controlled by individual features of an environment (Fenton et al, 2000; Rivard et al, 2004). It seems plausible then that the responses we report in superficial mEC may contribute in part or indeed wholly to those noted in the downstream hippocampus.…”
Section: Discussionmentioning
confidence: 99%